Examining the Role of Dyadic Coping on the Marital Adjustment of Couples Undergoing Assisted Reproductive Technology (ART) - Molgora, Sara; Fenaroli, Valentina; Acquati, Chiara; De Donno, Arianna; Baldini, Maria Pia; Saita, Emanuela (Frontiers in Psychology, 2019)
A couple is considered to be infertile if unable to conceive after 12 months of unprotected sexual intercourse. An extended body of literature supports that infertility and infertility treatments contribute to emotional, social, sexual, and relational issues that can have a negative impact on each partner’s well-being and on the couple relationship. Recent findings suggest that a dyadic approach should be used when working with couples coping with these stressors. However, most research to date has focused on the association between infertility and individual’s psychological outcomes, rather than on the experience of infertility-related stress and coping from a relational perspective. Consequently, assuming that infertility is a dyadic stressor and that the ability of the partners to cope with this experience is the result of both individual and relational coping strategies, this study aimed to investigate dyadic coping and marital adjustment among couples at the beginning of an Assisted Reproductive Technology (ART) treatment. A sample of 167 heterosexual couples (N= 334) undergoing ART treatment at the fertility clinic of a large hospital in Milan from January to December 2017 was recruited. Each participant completed self-reported questionnaires examining marital adjustment (Dyadic Adjustment Scale) and dyadic coping (Dyadic Coping Questionnaire). Demographics and clinical variables were also collected. Data were analysed using the Actor Partner Interdependence Model (APIM), testing the effect of each partner’s dyadic coping style on their own and their partner’s marital adjustment. Results revealed that both women and partners’ scores on positive dyadic coping styles (common, emotion-focused, problem-focused, and delegated dyadic coping) contributed to higher marital adjustment. This result suggests that couples unable to engage in these type of reciprocal supportive behaviors and those unsatisfied with their coping efforts may be more vulnerable while undergoing ART treatments. Furthermore, findings highlighted some gender differences for stress communication and negative dyadic coping suggesting the presence of specific dynamics within couples facing an ART treatment. Implications for clinical practice and future research are discussed.